NO dismutase activity of seven-coordinate manganese(II) pentaazamacrocyclic complexes - Filipovic, Milos; Dürr, Katharina L.; Mojovic, Milos; Simeunovic, Vladica; Zimmermann, Robert; Nicetic, Vesna; Ivanovic-Burmazovic, Ivana (Angewandte Chemie International Edition, 2008)
Redox selectivity? Seven-coordinate manganese(II) pentaazamacrocyclic complexes stimulate NO disproportionation by a novel dismutation mechanism based on the formation of labile metal-nitrosyl adducts and which is associated with the Mn/Mn redox cycle. The metal-bound NO in these aducts has the character and reactivity of NO and NO species. Ex vivo studies suggest that superoxide dismutase mimics of this kind could interfere with NO-mediated processes in biological milieu. (Chemical Equation Presented) © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.